2011
DOI: 10.1016/j.febslet.2011.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Parsing a multifunctional biosynthetic gene cluster from rice: Biochemical characterization of CYP71Z6 & 7

Abstract: Rice (Oryza sativa) contains a biosynthetic gene cluster associated with production of at least two groups of diterpenoid phytoalexins, the antifungal phytocassanes and antibacterial oryzalides. While cytochromes P450 (CYP) from this cluster are known to be involved in phytocassane production, such mono-oxygenase activity relevant to oryzalide biosynthesis was unknown. Here we report biochemical characterization demonstrating that CYP71Z6 from this cluster acts as an ent-isokaurene C2-hydroxylase that is presu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 24 publications
(83 reference statements)
1
78
0
1
Order By: Relevance
“…This search identified a member of the CYP71 family, ZmCYP71Z16, which showed high protein sequence similarity (89%) to the recently reported maize ZmCYP71Z18 involved in zealexin biosynthesis . Phylogenetic analysis placed ZmCYP71Z16 adjacent to ZmCYP71Z18 within a clade that also contained the rice P450s CYP71Z1, CYP71Z6, and CYP71Z7, of which CYP71Z6 and CYP71Z7 catalyze reactions in oryzalide and phytocassane biosynthesis (Wu et al, 2011;Fig. 3).…”
Section: Zmksl4 Produces An Unusual Diterpene Scaffoldmentioning
confidence: 99%
“…This search identified a member of the CYP71 family, ZmCYP71Z16, which showed high protein sequence similarity (89%) to the recently reported maize ZmCYP71Z18 involved in zealexin biosynthesis . Phylogenetic analysis placed ZmCYP71Z16 adjacent to ZmCYP71Z18 within a clade that also contained the rice P450s CYP71Z1, CYP71Z6, and CYP71Z7, of which CYP71Z6 and CYP71Z7 catalyze reactions in oryzalide and phytocassane biosynthesis (Wu et al, 2011;Fig. 3).…”
Section: Zmksl4 Produces An Unusual Diterpene Scaffoldmentioning
confidence: 99%
“…This was originally attempted using the native genes, obtained from the KOME rice cDNA database (Kikuchi et al, 2003). Due to our previous successful expression of plant CYP in Escherichia coli (Swaminathan et al, 2009;Morrone et al, 2010a;Wang et al, 2011;Wu et al, 2011), this was carried out using our bacterial modular metabolic engineering system (Cyr et al, 2007). In particular, by coexpression with the requisite CYP reductase (CPR) and functional pairings of upstream CPS and KS(L) to produce all of the labdane-related diterpenes found in rice (see Supplemental Fig.…”
Section: Recombinant Expressionmentioning
confidence: 99%
“…Codon optimization has been reported to increase expression efficiency of plant CYP (Chang et al, 2007), and we have found that complete gene recoding to optimize codon usage for expression in E. coli can lead to activity when none was observed with the native gene sequence Wu et al, 2011). Thus, we had such gene constructs synthesized for OsKOL4 and OsKOL5.…”
Section: Recombinant Expressionmentioning
confidence: 99%
“…Unknown products were purified via flash chromatography and HPLC, much as has been previously described (9,10,17,19,(26)(27)(28), with further details available in the SI Appendix. The resulting compounds were then resuspended in deuterated chloroform (CDCl 3 ) for structural analysis by NMR, as described in more detail in the SI Appendix.…”
Section: Methodsmentioning
confidence: 99%